2014
DOI: 10.1002/bsl.2148
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Differential Mnemonic Effects of False Denials and Forced Confabulations

Abstract: Citation:Otgaar, H., Howe, M. L., Memon, A. & Wang, J. (2014). The development of differential mnemonic effects of false denials and forced confabulations. Behavioral Sciences and the Law, 32(6), pp. 718-731. doi: 10.1002/bsl.2148 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AbstractThe current experiment was designed to assess the mnemonic consequences of false denials and forced confabulations. Children (6-to 8-and 10-to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

8
2

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 49 publications
3
76
0
Order By: Relevance
“…There are several forensically relevant contexts in which lying about what one remembers may occur. For example, victims of sexual abuse often delay disclosing an abusive experience through strategies such as falsely denying the abusive event altogether (Block et al, 2012;Goodman-Brown, Edelstein, Goodman, Jones, & Gordon, 2003;Sjöberg, & Lindblad, 2002; but see Lyon, 2007 andOtgaar, Howe, Memon, &Wang, 2014), which has put false denials at the forefront of discussions about sexual abuse allegations. Furthermore, false denials often are communicated by offenders trying to avoid culpability for a particular crime (e.g., Gudjonsson, Sigurdsson, & Einarsson, 2004).…”
Section: The Intimate Relationship Between Lying and Memorymentioning
confidence: 99%
“…There are several forensically relevant contexts in which lying about what one remembers may occur. For example, victims of sexual abuse often delay disclosing an abusive experience through strategies such as falsely denying the abusive event altogether (Block et al, 2012;Goodman-Brown, Edelstein, Goodman, Jones, & Gordon, 2003;Sjöberg, & Lindblad, 2002; but see Lyon, 2007 andOtgaar, Howe, Memon, &Wang, 2014), which has put false denials at the forefront of discussions about sexual abuse allegations. Furthermore, false denials often are communicated by offenders trying to avoid culpability for a particular crime (e.g., Gudjonsson, Sigurdsson, & Einarsson, 2004).…”
Section: The Intimate Relationship Between Lying and Memorymentioning
confidence: 99%
“…We have recently shown that denials can affect memory in a unique way (Otgaar, Howe, Memon, & Wang, 2014 ; Otgaar, Howe, Smeets, & Wang, 2016 ). In our experiments, participants were presented with some stimuli (e.g., a video), and after this, one group had to deny that certain details had been presented when in fact they had.…”
Section: The Effects Of Denial On Memorymentioning
confidence: 99%
“…Yet, in real life, sometimes witnesses lie intentionally. However, very few studies have examined the effects of deliberate lying on subsequent memory performance (for a few exceptions, see Colwell et al, 2011;Pickel, 2004;Polage, 2004Polage, , 2012Otgaar, Howe, Memon, & Wang, 2014;Vieira & Lane, 2013) The very few studies that investigated the effects of deliberate lying on memory reveal that the incorrect generated plausible information can sometimes be remembered more or at the same rate, as compared with a control group or control condition (Vieira & Lane, 2013;Pickel, 2004). For example, Pickel (2004) showed that participants who were deliberately asked to fabricate details about a perpetrator in a video remembered more incorrect details and less correct details than the control group.…”
mentioning
confidence: 99%